Business Cycles and Growth: A Survey - Paul Gaggl; Sandra Steindl (Austrian Institute of Economic Research (WIFO), 2007)
The paper surveys the evolution of modern macroeconomic models with the focus on the interrelations between endogenous growth and cyclical fluctuations. After reviewing models of the business cycle and endogenous growth, the paper discusses literature combining elements of both of them.
Keywords: 330; Business Cycles; Growth literature; survey; Konjunkturtheorie; Endogenes Wachstumsmodell; Theorie